The Influnece of Peat Layer on Hidrogen and Aluminium Concentration Originating from the Substratum Sulphidic Materials - Fahmi, Arifin Fahmi; Radjagukguk, Bostang; Purwanto, Benito Heru; Hanudin, Eko Hanudin (UNIVERSITY OF LAMPUNG, 2012)
Much of peatland in Indonesia has sulphidic materials as substratum. Soil acidity and metal elements in peatlandmay originate from the sulphidic materials which occur underneath of the peat layer. Peat soil buffering capacity andchelating ability of the peat materials regulate the soil acidity and metal solubility in the peatland. The study wasaimed to examine the influence of peat thickness and land hydrological conditions on the concentrations ofexchangeable aluminium (Al) and hidrogen (H) in the peatland. The study was carried out on peaty acid sulphatesoil, deep peat, moderate peat and shallow peat. Exchangeable Al and H were observed in the wet season, transitionfrom wet to dry season and dry season. The results showed that exchangeables of Al and H were mainly originatedfrom sulphidic material which were occured underneath of the peat layer. Peat layer had an important role on thesolubility of Al and H in the peatland. Peat thickness had influence on exchangeable-Al and H, 50 cm of the peatthickness (shallow peat) was the critical for peat function to reduce the Al and H solubility in the peatland. Hydrologicalcondition factor did not influence on the solubility of Al and H.Keywords: Aluminium; hydrogen; peatland; sulphidic materials[How to Cite: Fahmi A, B Radjagukguk, B Heru Purwanto and E Hanudin. 2012. The Influnece of Peat Layer on Hidrogen and Aluminium Concentration Originating from the Substratum Sulphidic Materials. J Trop Soils, 17 (3): 197-202. doi: 10.5400/jts.2012.17.3.197][Permalink/DOI: www.dx.doi.org/10.5400/jts.2012.17.3.197]